2021
DOI: 10.3390/atmos12010073
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Understanding of Reactive Mercury in Ambient Air: A Review

Abstract: This review focuses on providing the history of measurement efforts to quantify and characterize the compounds of reactive mercury (RM), and the current status of measurement methods and knowledge. RM collectively represents gaseous oxidized mercury (GOM) and that bound to particles. The presence of RM was first recognized through measurement of coal-fired power plant emissions. Once discovered, researchers focused on developing methods for measuring RM in ambient air. First, tubular KCl-coated denuders were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 78 publications
1
24
0
2
Order By: Relevance
“…Hg 0 is emitted to the atmosphere by mining, fuel combustion, and volcanism, and by volatilization of previously deposited Hg. , The Hg 0 oxidation pathways and the speciation of Hg II remain highly uncertain. The Br atom is considered to be a major Hg 0 oxidant. The oxidation of Hg 0 to Hg II by Br takes place in two steps, beginning with the formation of a BrHg I intermediate that then undergoes further oxidation to Hg II . NO 2 and HO 2 have been thought to be the main BrHg I oxidants, but the BrHg II ONO and BrHg II OOH products are rapidly photolyzed . Preliminary theoretical calculations by Saiz-Lopez et al show that BrHg I may react rapidly with ozone to produce a BrHg II O radical, which can then be stabilized to nonradical Hg II forms by subsequent reactions. , …”
Section: Introductionmentioning
confidence: 99%
“…Hg 0 is emitted to the atmosphere by mining, fuel combustion, and volcanism, and by volatilization of previously deposited Hg. , The Hg 0 oxidation pathways and the speciation of Hg II remain highly uncertain. The Br atom is considered to be a major Hg 0 oxidant. The oxidation of Hg 0 to Hg II by Br takes place in two steps, beginning with the formation of a BrHg I intermediate that then undergoes further oxidation to Hg II . NO 2 and HO 2 have been thought to be the main BrHg I oxidants, but the BrHg II ONO and BrHg II OOH products are rapidly photolyzed . Preliminary theoretical calculations by Saiz-Lopez et al show that BrHg I may react rapidly with ozone to produce a BrHg II O radical, which can then be stabilized to nonradical Hg II forms by subsequent reactions. , …”
Section: Introductionmentioning
confidence: 99%
“…To achieve the best RM collecting method, the Reno Atmospheric Mercury Intercomparison eXperiment (RAMIX) project investigated different RM adsorption surfaces (e.g., nylon membrane, KCl-denuder, and cation exchange membrane (CEM)) and selected CEM as the best surface to collect RM in both laboratory and field experiments. , Based on the performance of the CEM, a Reactive Mercury Active System was developed to collect almost all RM, which was believed to greatly improve the accuracy of RM measurement. Collecting and analyzing Hg 2+ /RM on CEM requires at least one week of sampling to ensure a sufficient amount of Hg for analysis . Lyman et al incorporated CEM with an online pyrolizer-based method and achieved separated measurement of RM and Hg 0 in 20 min .…”
Section: Introductionmentioning
confidence: 99%
“…We also evaluated our GOM observed results based on this method and found that the bias in our observations appeared to be negligible (see details in the supplementary information). In fact, Gustin's recent review paper also suggested that "We expect that KCl-denuder derived data is best for polar regions or high elevation locations in the free troposphere for these areas are dominated by halogenated compounds and dry air" in Section 6 of this paper (Gustin et al, 2021). In summary, we think that the uncertainty of GOM measurement from the Tekran system may not fundamentally change our main discussion and conclusions in this study based on our evaluations of GOM data, and we caution that the GOM results reported in this study should be considered as the lower limits of atmospheric GOM (Wang et al, 2014).…”
Section: Measurements Of Atmospheric Mercurymentioning
confidence: 86%